Essays on aggregate dynamics: externalities, liquidity and financial crises - Ochiai, Hiroshi (2012)
In the second chapter, we consider a mechanism of unstable fluctuations of aggregate investments by means of a global game approach. For this purpose, we extended a static global game to a dynamic one and paid attention to the effect of past aggregate investments on current profitability. Once this effect of aggregate investments between periods is taken into account, we can show that firms’ equilibrium strategies of investments become highly volatile over time. Moreover, long persistence of high or low economic activity can be explained by this model as well.